Comparison of perceived exercise intensity and objective exercise intensity during a freestyle wrestling match - Chino, K.; Matsumoto, S.; Ikeda, T.; Yanagawa, Y. (International Journal of Wrestling Science, 2014)
This study compared perceived exercise intensity and objective exercise intensity during a freestyle wrestling match. Twelve elite collegiate male wrestlers performed freestyle wrestling matches with three 2-min periods. Perceived exercise intensity and objective exercise intensity were evaluated by the 6-20 point Borg rating of perceived exertion (RPE) scale and heart rate (HR), respectively. To compare these values directly, three methods were used: (1) comparison of RPE increased by 10 times and HR (method-1); (2) classification of five exercise intensities (very light, 1; near-maximal to maximal, 5) (method-2); and (3) classification of seven exercise intensities (very light, 1; near-maximal to maximal, 7) by subdividing scales in method-2 (method-3). Perceived exercise intensity was significantly lower than objective exercise intensity in each period (all P < 0.05, method-1), in the first period (P = 0.007, method-2), or in the first and second periods (all P < 0.01, method-3). Perceived exercise intensity of the winners was significantly lower than that of the losers (P = 0.04, method-1; P = 0.03, method-2), but objective exercise intensity was not significantly different between them. These results suggest that wrestlers, especially winners, feel lower exercise intensity compared with actual exercise intensity during a wrestling match.